Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
Unfortunately, we start this issue of PINS with a comment about the irrational. Not the irrational as that uncanny object of psychoanalytic discourse, but the irrational as seemingly rational public discourse. The public discourse of educational policy and the control of knowledge as embodied in the SAPSE system is what is being referred to. In the editorial of PINS 17 (1993), we mentioned that PINS was first turned down for SAPSE accreditation during 1992 for the following reason: "Not a research journal. Articles are mostly for the practitioner eg case studies, general review on a specific field of knowledge, etc". The procedure for accreditation is that academics, or university research offices on academics’ behalf, make submissions to the State Department of Education for the inclusion of any journal/s onto the SAPSE subsidy list. Journals themselves may not apply directly. The success or failure of accreditation is communicated to the universities, and again, not to the journal/s.